2010
DOI: 10.1002/mnfr.200900397
|View full text |Cite
|
Sign up to set email alerts
|

Tocopherol production in plant cell cultures

Abstract: Tocopherols, collectively known as vitamin E, are lipophilic antioxidants, essential dietary components for mammals and exclusively synthesized by photosynthetic organisms. Of the four forms (alpha, beta, gamma and delta), alpha-tocopherol is the major vitamin E form present in green plant tissues, and has the highest vitamin E activity. Synthetic alpha-tocopherol, being a racemic mixture of eight different stereoisomers, always results less effective than the natural form (R,R,R) alpha-tocopherol. This raises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 29 publications
3
30
0
2
Order By: Relevance
“…α-Tocopherol, which is the most active isoform of vitamin E (Caretto et al 2009), was the predominant isoform in all the leafy vegetables analysed. However, as it will be described below, in the four wild asparagus studied other forms were also codominant or even predominant.…”
Section: Tocopherols Compositionmentioning
confidence: 96%
See 1 more Smart Citation
“…α-Tocopherol, which is the most active isoform of vitamin E (Caretto et al 2009), was the predominant isoform in all the leafy vegetables analysed. However, as it will be described below, in the four wild asparagus studied other forms were also codominant or even predominant.…”
Section: Tocopherols Compositionmentioning
confidence: 96%
“…Moreover, it has been considered the most active form in humans due to a preferential absorption and distribution of this compound in the human body (Caretto et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…When Geipel et al [52] characterized the production of α-tocopherol using photomixotrophic and heterorotrophic sunflower SCC, they found that the highest intracellular α-tocopherol levels (77 µg gDW -1 ) were obtained with a photomixotrophic cell culture grown in liquid MS supplemented with 0,5 mg L -1 naphthalene acetic acid, 0,5 mg L -1 benzylaminopurine, 15 g L -1 sucrose and maintained at 26 ºC and a light intensity of 125 µmol m -2 s -1 . Likewise, sunflower and tobacco SCC produced 24 µg gFW -1 and 41 µg gFW -1 of α-tocopherol when 150 µM homogentisic acid alone or in combination with 200 µM phytol was added, respectively [55,54]. Moreover, Caretto et al [55] analyzed the levels of α-tocopherol obtained from different sunflower sources and observed a production level of 11,4 µg gFW -1 (100 µg gDW -1 ), 7,3 µg gFW -1 (70 µg gDW -1 ), 18,1 µg gFW -1 (180 µg gDW -1 ), and 24 µg gFW -1 (239 µg gDW -1 ) in tissues of hypocotyls, stems, leaves and SCC, respectively.…”
Section: Effect Of Cds On α-Tocopherol and Chlorophyll Content Of Grementioning
confidence: 99%
“…Likewise, sunflower and tobacco SCC produced 24 µg gFW -1 and 41 µg gFW -1 of α-tocopherol when 150 µM homogentisic acid alone or in combination with 200 µM phytol was added, respectively [55,54]. Moreover, Caretto et al [55] analyzed the levels of α-tocopherol obtained from different sunflower sources and observed a production level of 11,4 µg gFW -1 (100 µg gDW -1 ), 7,3 µg gFW -1 (70 µg gDW -1 ), 18,1 µg gFW -1 (180 µg gDW -1 ), and 24 µg gFW -1 (239 µg gDW -1 ) in tissues of hypocotyls, stems, leaves and SCC, respectively.…”
Section: Effect Of Cds On α-Tocopherol and Chlorophyll Content Of Grementioning
confidence: 99%
“…Alfatocopherol, the chemical form with the highest vitamin E activity (Caretto, Nisi, Paradiso, & DeGara, 2009), was the most abundant one in all the studied samples (Table 3), except for Silybum marianum whose predominant form was δ-tocopherol As shown in Table 3, Cichorium intybus presented the highest total tocopherols content (2.98 mg/100 g), followed by Sonchus oleraceus (2.22 mg/100 g), while Scolymus hispanicus and Silybum marianum again stood out for their lowest contents (0.05 mg/100 g and 0.15 mg/100 g, respectively), which may be related to the fact that these samples are peeled leaves, only containing midrib tissues.…”
Section: Tocopherols Compositionmentioning
confidence: 99%